Universe revealed [videorecording (DVD)] - Williams, Talithia (BBC, 2021)
"In distant realms far beyond the familiar solar system, an epic drama is playing out, with a cast list featuring rogue planets, colliding galaxies, and black holes more massive than a billion suns, and each character has its own extraordinary story to tell. In this five-part series, NOVA delves into the vastness of space to capture moments of high drama when the universe changed forever. State-of-the-art animation gives us astonishing, photorealistic glimpses of the birth of a star in a stellar nursery, the chaos created as two galaxies collide, and the power of a supermassive black hole as it flings a star across space so violently that it's still traveling 10 million years later. NOVA even takes viewers back on the ultimate time travel voyage, to witness the birth of space and time itself. Informed by huge advances in scientific understanding, the series brings us face-to-face with the most surprising characters in the cosmos and reveals how their fates are intertwined with our own. Take a ringside seat for the greatest show in the universe"--Container.